Electrodeposition method and application of zinc selenide composite interface layer modified zinc negative electrode

By constructing a composite interface layer of zinc selenide on the zinc negative electrode of zinc ion battery, the combination of carbon nanotubes and zinc selenide is used to solve the problems of zinc dendrites growth and side reactions, and the stability and cycle life of zinc negative electrode are improved.

CN119913510APending Publication Date: 2025-05-02HANGZHOU VOCATIONAL & TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510058563.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The zinc negative electrode of zinc ion battery faces problems such as zinc dendrites growth, side reactions and corrosion passivation during charging and discharging, resulting in poor circulation stability.

Method used

By constructing a composite interface layer of zinc selenide on the zinc negative electrode, the combination of carbon nanotubes and zinc selenide is used to limit the free water molecules at the interface, inhibit the water-induced side reactions, promote the uniform migration of Zn2+, and inhibit the growth of zinc dendrites.

Benefits of technology

The mechanical stability of the zinc negative electrode is achieved, the growth of zinc dendrites is inhibited, the electron transmission efficiency is improved, the structural stability and interface performance are enhanced, and the cycle life of the zinc battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913510A_ABST
    Figure CN119913510A_ABST
Patent Text Reader

Abstract

The invention provides an electro-deposition method and application of a zinc selenide composite interface layer modified zinc negative electrode, and belongs to the technical field of zinc batteries. The preparation method comprises the following steps: dissolving a carbon nano tube and polyvinylidene fluoride in N-methyl pyrrolidone to form a carbon nano tube solution; coating the surface of the zinc foil with the carbon nanotube solution, and drying; and carrying out electro-deposition by taking the dried zinc foil as a working electrode of an electro-deposition tank, a platinum electrode as a counter electrode, a saturated calomel electrode as a reference electrode and a mixture of a zinc sulfate solution and a Se solution as a deposition working solution, taking out the working electrode, cleaning and drying to obtain a finished product of the modified zinc negative electrode with the zinc selenide composite interface layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an electro-deposition method for a zinc negative electrode modified by a zinc selenide composite interface layer and its application, belonging to the technical field of zinc batteries. Background Art

[0002] As a developing energy storage technology, zinc-ion batteries have attracted widespread attention for their safety, moderate energy density, and abundant zinc metal reserves. In addition, zinc-ion batteries also show significant advantages in energy storage. Their unique two-electron redox process can give the battery an extremely high theoretical capacity, with a mass specific capacity of up to 820 mAh g -1 The volumetric capacity has reached 5849 mAh cm -3 At the same time, the equilibrium potential of zinc is relatively low, only 0.76 V (relative to the standard hydrogen electrode SHE), and its hydrated ion radius is small. These characteristics together promote the rapid diffusion and efficient transport of ions inside the battery.

[0003] However, the negative electrode of zinc-ion batteries, zinc metal, faces many challenges during the charging and discharging process. The growth of zinc dendrites may not only cause internal short circuits in the battery, but also reduce the battery's cycle efficiency; while corrosion and hydrogen evolution side reactions will produce byproducts such as zinc hydroxysulfate, leading to battery passivation, thereby seriously weakening the reversibility of the zinc negative electrode. The above problems greatly limit the cycle stability of zinc-ion batteries. Therefore, how to effectively inhibit the growth of zinc dendrites, control the hydrogen evolution reaction, and prevent the corrosion and passivation of metal zinc have become hot spots and difficulties in the current research field of zinc-ion batteries. Summary of the invention

[0004] In view of this, the present application provides a method for electro-deposition of a zinc negative electrode modified with a zinc selenide composite interface layer, which provides the zinc negative electrode with a modified zinc selenide composite interface layer, and the zinc selenide composite interface layer has good mechanical stability and is not easily damaged during the continuous charge and discharge process. It can not only limit the free water molecules on the interface and inhibit the side reactions induced by water; it can also promote the Zn 2+ Migrate evenly on the electrode surface and inhibit the growth of zinc dendrites.

[0005] Specifically, the present application is implemented through the following scheme: A method for electro-deposition of a zinc selenide composite interface layer modified zinc negative electrode, the steps are as follows: Step 1, dissolving carbon nanotubes and polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) to form a carbon nanotube solution; Step 2, coating the carbon nanotube solution on the surface of the zinc foil and drying; Step 3, using the dried zinc foil in step 2 as the working electrode of the electrodeposition tank, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and using a mixture of zinc sulfate solution and Se solution as the deposition working solution for electrodeposition, wherein the concentration of zinc sulfate solution is 0.15±0.05 M, and the concentration of Se ions is 0.01~0.1 mM; Step 4: Take out the working electrode, clean it, and dry it to obtain a finished modified zinc negative electrode with a zinc selenide composite interface layer.

[0006] The above scheme aims to solve the two technical problems of zinc dendrites and side reactions in the field of zinc ion batteries. The zinc negative electrode material with a carbon nanotube modified layer is realized by electrochemical deposition. The process is simple, the process is easy to control, the preparation time is short, and a high single yield can be achieved, which is conducive to large-scale production.

[0007] Further, as a preference: In step 1, the concentration of carbon nanotubes in the carbon nanotube solution is 0.01-10 mg / mL.

[0008] In step 2, The zinc foil is obtained by the following pretreatment: after the commercial zinc foil is polished to remove the passivation layer, it is first washed with deionized water, then ultrasonically treated with ethanol, and dried to obtain the zinc foil. More preferably, the washing times are 3 to 5 times, and the ultrasonic treatment time is 10 to 30 minutes. The drying temperature is 60 to 80 ° C, and the drying time is 5 to 30 minutes.

[0009] The coating is carried out in the following manner: the zinc foil is placed on a spin coater, and the melt is evenly distributed on the surface of the zinc foil through the rotation of the spin coater. More preferably, the rotation speed of the spin coater is 300-500 rmp, and the rotation time is 5-10 s, so as to control the thickness of the coating to be maintained at 5-10 microns. The spin coating method is realized by the spin coater to achieve precise control of the interface layer, and the interface layer remains stable after the battery is charged and discharged thousands of times.

[0010] In step three, The pH of the deposition working solution is 4.5-6.0, the electrodeposition is carried out at room temperature, the voltage is -1.5-0.5 V, the current is 1-10 mA, and the electrodeposition time is 20-40 min. The unique setting of the electrodeposition method is used to improve the performance of zinc ion batteries, improve the interface characteristics of the zinc negative electrode and the electrolyte, and enable the product to have higher coulombic efficiency and longer cycle life.

[0011] Preparation method of Se solution: SeO 2 The powder was added with concentrated sulfuric acid and mixed evenly, and then deionized water was added and stirred, and a Se solution was obtained by gradient dilution.

[0012] The zinc sulfate solution is obtained by dissolving zinc sulfate heptahydrate in deionized water.

[0013] The concentration of the zinc sulfate solution is 0.15 M, and the concentration of Se ions is 0.05 mM.

[0014] In step 4, the number of times of washing is 3 to 4 times, and the washing can be cross-cleaned with deionized water and anhydrous ethanol. The drying temperature is 50 to 80°C, and the drying time is 5 to 30 minutes.

[0015] The working principle and beneficial effects of the present invention are summarized as follows: First, this interface layer can inhibit the growth of zinc dendrites. During the charge and discharge of zinc-ion batteries, zinc dendrites are a prominent problem. The unique nanostructure and high specific surface area of ​​carbon nanotubes, combined with the specific crystal structure and surface characteristics of zinc selenide, can induce zinc ions to deposit in a highly oriented manner along specific crystal planes on the negative electrode surface. This orderly deposition method can form a more uniform and dense deposition layer of zinc during the charge and discharge process, avoiding the problem of dendrite growth caused by uneven deposition of zinc ions.

[0016] Secondly, the electron transmission efficiency is improved. Both carbon nanotubes and zinc selenide have excellent conductivity. They can build a fast electron transmission channel in the zinc negative electrode, accelerate electron transfer, optimize electrode reaction kinetics, and allow the battery to efficiently transmit electrons during the charge and discharge process, especially at high rate charge and discharge, thereby improving the battery's charge and discharge efficiency and rate performance, and meeting the needs of use in more scenarios.

[0017] Finally, it helps to enhance structural stability and improve interface performance. The good mechanical properties of the composite interface layer can strengthen the overall structure of the zinc negative electrode material, buffer the volume change stress during charge and discharge, prevent the electrode material from pulverizing and falling off, and maintain the integrity of the electrode.

[0018] The above scheme promotes the uniform migration of zinc ions on the electrode surface to form a uniform coating by constructing a stable composite interface layer on the zinc negative electrode, thereby greatly improving the reversibility and stability of zinc in the dissolution / deposition process. Therefore, the applicant also provides an application of the zinc selenide composite interface layer modified zinc negative electrode obtained by the above electrodeposition method in zinc batteries, the zinc batteries include but are not limited to zinc-zinc symmetrical batteries, zinc-titanium half-cells and V 2 O 5 The assembled full battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0020] Figure 1 This is a scanning microscope image of the modified zinc negative electrode prepared in this application; Figure 2 This is a corrosion reaction test diagram of the modified zinc negative electrode prepared in this application; Figure 3 The coulombic efficiency diagram of the modified zinc negative electrode prepared in this application for zinc-titanium half-cell; Figure 4 The performance diagram of the prepared modified zinc negative electrode used in zinc-zinc symmetric battery; Figure 5 The performance diagram of the prepared modified zinc anode for full battery; Figure 6 This is the charge and discharge curve of the prepared modified zinc negative electrode used in the full battery. DETAILED DESCRIPTION

[0021] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0022] Example 1

[0023] The present application provides a method for electro-deposition of a zinc selenide composite interface layer modified zinc negative electrode, the specific process is as follows: (1) Use sandpaper to remove the oxide layer on the surface of a 5 cm × 5 cm zinc foil, wash it with deionized water for three times, put it in anhydrous ethanol for ultrasonic treatment for 30 min, and then dry it in a vacuum drying oven at 60 °C for 20 min to obtain a spare zinc foil.

[0024] (2) Dissolve carbon nanotubes and PVDF in NMP in a certain proportion to form a uniform carbon nanotube solution.

[0025] (3) Place the zinc foil on a spin coater and rotate the substrate to evenly distribute the solution on the surface of the zinc foil. Control the rotation speed and time to control the thickness and uniformity of the film.

[0026] (4) Add 10.8 g of zinc sulfate heptahydrate into a 250 mL beaker, then add 100 mL of deionized water. After ultrasonic treatment until completely dissolved, pour into a 250 mL volumetric flask and add deionized water to make up to volume to obtain 250 mL of 0.15 M zinc sulfate solution.

[0027] (5) Add 20 mg of SeO 2 Add the powder to a 500 mL beaker, pipette 1 mL of concentrated sulfuric acid into the beaker, and repeat the pipetting 5 times until SeO 2 The powder was completely dissolved, and then 100 mL of deionized water was added and magnetic stirring was performed for 30 min. After complete dissolution, it was transferred to a 250 mL volumetric flask and deionized water was added to make up the volume to obtain 250 mL of Se solution with a concentration of 0.5 mM.

[0028] (6) Add 10 mL of 0.5 mM Se solution into a 100 mL volumetric flask and add deionized water to make up to volume to obtain a diluted Se solution with a concentration of 0.05 mM.

[0029] (7) Add 60 mL of the 0.15 M zinc sulfate solution obtained in step (4) and 60 mL of the 0.05 M Se solution obtained in step (6) into the electrolysis working cell and mix them evenly to obtain a deposition working solution.

[0030] (8) Start the electrochemical workstation and open the chi660e.exe program. Select "Setup" and then "HardwareSest". After the hardware integrity check is completed, select "Setup" and then "Sechnique" and then select the mode "Amperometrici-t Curve". After the selection is completed, select "Setup" and then "ParameSers". After completion, start setting the test parameters. The parameters are as follows: Init E (V): 1 V; Smpl Intvl (V): 0.1; Run Time (s): 1800; Quiet Time (s): 0; Sensitvit (A / V): 1.e-0.01.

[0031] (9) Control the electrodeposition time and set the deposition time to 40 min to obtain a film of the desired thickness.

[0032] (10) After the electrodeposition is completed, turn off the power supply and remove the working electrode. The deposited film is washed with deionized water and anhydrous ethanol three times, and then dried in an oven at 70 °C for 15 min. The obtained material is recorded as ZnSe@CNT material.

[0033] The performance of the obtained ZnSe@CNT material was tested, and the results are as follows: Depend on Figure 1 It can be observed that the zinc selenide composite interface layer modified zinc negative electrode ZnSe@CNT prepared by electrodeposition in this embodiment is in a uniform state.

[0034] Depend on Figure 2 From the corrosion reaction test diagram, it can be observed that by adopting a three-electrode system, the scanning voltage range is between -1.25V and -0.65V, and the scanning rate is fixed at 10mV s −1 When the modified zinc negative electrode obtained by the electrodeposition method of the present invention has a lower corrosion current density and a more positive corrosion potential in the corrosion reaction test, it can be shown that the modification in this case inhibits the occurrence of side reactions.

[0035] Depend on Figure 3 The coulombic efficiency diagram shows that the zinc anode modified by the zinc selenide composite interface layer prepared in this embodiment is used in a zinc-titanium half-cell. When the current density is 1 mA cm −2 , with a capacity of 0.5 mAh cm −2 The zinc-titanium half-cell showed a very stable Coulombic efficiency value within 220 hours, with an average value of 98.92%, demonstrating good cycle reversibility.

[0036] Depend on Figure 4 It can be seen from the battery performance diagram that the zinc selenide composite interface layer modified zinc negative electrode prepared in this embodiment is used for zinc-zinc symmetric battery. When the current density is 10 mA cm -2 When the capacity is 2 mAh cm -2 The cycle life of the zinc-zinc symmetrical battery can exceed 1200 hours, far exceeding the life of a pure zinc battery.

[0037] Depend on Figure 5 , Figure 6 From the performance graph and charge-discharge curve of the full battery, it can be seen that the constant current charge-discharge curves (GCD) of different full batteries show the same shape, which means that the composite interface layer will not affect the redox process of the cathode material. GCD further confirms that the voltage hysteresis of the full battery modified by us is smaller, that is, the full battery modified by the zinc selenide composite interface layer modified zinc negative electrode ZnSe@CNT prepared by electrodeposition in this embodiment has a smaller polarization voltage. When the current density is 1 A g -1 When the zinc selenide composite interface layer prepared in this embodiment modifies the zinc negative electrode and V 2 O 5 The assembled full battery can provide about 175 mAh g -1 The initial specific capacity and ultra-long life of more than 1500 cycles.

[0038] The following experiments were conducted on the influence of the core parameters in electrodeposition, as follows Example 2

[0039] The configuration of this embodiment is the same as that of embodiment 1, except that in step (1), the drying temperatures are replaced with 60°C, 62°C, 64°C, 65°C, 68°C, 71°C, 75°C, 77°C, 79°C, and 80°C, respectively.

[0040] Example 3

[0041] The configuration of this embodiment is the same as that of embodiment 1, except that in step (1), the drying time is replaced by 5 min, 8 min, 10 min, 12 min, 14 min, 16 min, 19 min, 20 min, 23 min, 25 min, 28 min, 29 min, and 30 min, respectively.

[0042] Example 4

[0043] The configuration of this embodiment is the same as that of embodiment 1, except that in step (1), the number of times of washing with deionized water can be 3 or 5 times.

[0044] Example 5

[0045] The configuration of this embodiment is the same as that of embodiment 1, except that in step (8), the deposition voltages are replaced by -1.4 V, -1.2 V, -1.0 V, -0.8 V, -0.6 V, -0.4 V, -0.2 V, 0.2 V, and 0.4 V, respectively.

[0046] Example 6

[0047] The configuration of this embodiment is the same as that of embodiment 1, except that in step (5), the drying temperatures are replaced with 60°C, 62°C, 64°C, 65°C, 68°C, 71°C, 75°C, 77°C, 79°C, and 80°C, respectively.

[0048] Example 7

[0049] The configuration of this embodiment is the same as that of embodiment 1, except that in step (9), the deposition time is replaced by 5 min, 8 min, 10 min, 12 min, 14 min, 16 min, 19 min, 20 min, 23 min, 25 min, 28 min, 29 min or 30 min, respectively.

[0050] Example 8

[0051] The configuration of this embodiment is the same as that of embodiment 1, except that in step (10), the washing times of deionized water and anhydrous ethanol can be 2 times.

[0052] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.

Claims

1. A method for electrodeposition of a zinc selenide composite interface layer modified zinc negative electrode, characterized in that: Here are the steps: Step 1, dissolving carbon nanotubes and polyvinylidene fluoride in N-methylpyrrolidone to form a carbon nanotube solution; Step 2, coating the carbon nanotube solution on the surface of the zinc foil and drying; Step 3, using the dried zinc foil in step 2 as the working electrode of the electrodeposition tank, the platinum electrode as the counter electrode, the saturated calomel electrode as the reference electrode, and using a mixture of zinc sulfate solution and Se solution as the deposition working solution for electrodeposition, wherein the concentration of zinc sulfate solution is 0.15±0.05 M, and the concentration of Se ions is 0.01~0.1 mM; Step 4: Take out the working electrode, clean it, and dry it to obtain a finished modified zinc negative electrode with a zinc selenide composite interface layer.

2. The method for electro-deposition of a zinc selenide composite interface layer modified zinc negative electrode according to claim 1, characterized in that: In step 1, the concentration of carbon nanotubes in the carbon nanotube solution is 0.01-10 mg / mL.

3. The method for electro-deposition of a zinc selenide composite interface layer modified zinc negative electrode according to claim 1, characterized in that: In step 2, the zinc foil is obtained by the following pretreatment: the commercial zinc foil is polished to remove the passivation layer, washed with deionized water, and then placed in ethanol for ultrasonic treatment and dried to obtain the zinc foil.

4. The method for electro-deposition of a zinc selenide composite interface layer modified zinc negative electrode according to claim 1, characterized in that: The coating is carried out in the following manner: a zinc foil is placed on a spin coater, and the melt is evenly distributed on the surface of the zinc foil through the rotating substrate of the spin coater.

5. The method for electro-deposition of a zinc selenide composite interface layer modified zinc negative electrode according to claim 4, characterized in that: The rotation speed of the spin coater was 300-500 rpm and the rotation time was 5-10 s to control the coating thickness to be maintained at 5-10 μm.

6. The method for electro-deposition of a zinc selenide composite interface layer modified zinc negative electrode according to claim 1, characterized in that: In step three, the pH of the deposition working solution is 4.5-6.0, the electrodeposition is carried out at room temperature, the voltage is -1.5-0.5 V, the current is 1-10 mA, and the electrodeposition time is 20-40 min.

7. The method for electro-deposition of a zinc selenide composite interface layer modified zinc negative electrode according to claim 1, characterized in that: In step 3, the Se solution is prepared by adding concentrated sulfuric acid to SeO2 powder and mixing evenly, then adding deionized water and stirring, and gradient diluting to obtain a Se solution.

8. The method for electro-deposition of a zinc selenide composite interface layer modified zinc negative electrode according to claim 1, characterized in that: In step 3, the concentration of zinc sulfate solution is 0.15 M, and the concentration of Se ion is 0.05 mM.

9. Use of a zinc negative electrode modified with a zinc selenide composite interface layer obtained by the method of claim 1 in a zinc battery.

10. The use of a zinc selenide composite interface layer modified zinc negative electrode in a zinc battery according to claim 9, characterized in that: The zinc battery includes but is not limited to a zinc-zinc symmetric battery, a zinc-titanium half-cell, and a full battery assembled with V2O5.